Vietnam : Asia's emerging economy - Tan, See Yun (2014)
The mission of this project is to provide a comprehensive, all rounded and up to date guide to first time foreign investors venturing into the Vietnamese economy, equipping them with the essential and vital knowledge to make strategic and timely investment decisions.